Fenomema Prank dan Pengaruhnya Terhadap Spiritualitas Generasi Milenial - Dominggus, Dicky (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2022)
Lately, society have been shocked by the phenomenon of pranks done by teenagers. Various kinds of pranks are done for the sake of entertaining only. Doing pranks as entertainment or show will certainly affect the spiritual growth of the millennials. This research aims to find the motives behind the practice of pranks and see its effects on the spiritual growth of the millennial generation. This research is a qualitative research with interview method. The interviews discovered what are the motives of the informants to do pranks, what do they feel when doing pranks and also their views on the fairness of pranking. This research shows that pranking is based on seeking entertainment or jokes, following friend’s examples and making memories. But pranks are also done to boost popularity. Having pranks as entertainment or show will certainly affect the spiritual growth of the millennials because telling lies are the part of pranking. This of course will have a long-term impact, that is moral degradation. Pranks have two inseparable sides; Prank can be entertainment but on the other hand it can be negative if it has a negative impact and harms others. For this reason, it is necessary for teenagers to be wise in doing pranks. It can be done for the sake of entertaining only and not to harm others.